2009
DOI: 10.1302/0301-620x.91b6.22284
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral nerves of the upper limb with ultrasonography

Abstract: We prospectively studied 26 consecutive patients with clinically documented sensory or motor deficiency of a peripheral nerve due to trauma or entrapment using ultrasound, and in 19 cases surgical exploration of the nerves was undertaken. The ultrasonographic diagnoses were correlated with neurological examination and the surgical findings. Reliable visualisation of injured nerves on ultrasonography was achieved in all patients. Axonal swelling and hypoechogenity of the nerve was diagnosed in 15 cases, loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 14 publications
1
10
0
2
Order By: Relevance
“…High-frequency ultrasound is the most widely used method to directly observe the morphology of the peripheral nerve6. High-frequency ultrasound is noninvasive and easily accepted by patients, which is beneficial for multiple dynamic follow-ups after repair of the peripheral nerve.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency ultrasound is the most widely used method to directly observe the morphology of the peripheral nerve6. High-frequency ultrasound is noninvasive and easily accepted by patients, which is beneficial for multiple dynamic follow-ups after repair of the peripheral nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies correlating sonographic findings with surgical exploration have demonstrated the ability to distinguish between various types of nerve injury, ranging from simple contusions with fusiform thickening of the nerve to partial tears or complete lacerations. [6][7][8] This information has a profound impact for both the surgeon and the patient, as many humeral fractures are treated with closed reduction, with low rates of malunion, although there is a 10% to 32% risk of developing secondary radial nerve palsy with intervention. 9 As such, the decision to pursue surgical intervention for treatment of the nerve injury may be guided by the sonographic results.…”
Section: Unique Utility Of Sonography For Detection Of An Iatrogenic mentioning
confidence: 99%
“…The performance and accuracy of sonography are user dependent, and the depth of the nerve proximally may somewhat limit diagnostic evaluation. It has been shown that at a depth of greater than 3 cm, spatial resolution becomes limited in evaluation of the radial nerve 8 …”
mentioning
confidence: 99%
“…The normal echogenicity of the nerves is between the relatively low echogenicity of muscle and the higher echogenicity of the tendon (23,26).…”
Section: Nervesmentioning
confidence: 99%
“…First, US examinations are operator dependent and require an experience in superficial soft tissue structures, which have a relatively long learning curve. Second, postoperative and/or posttraumatic subcutaneous air, suture materials, and deteriorating soft tissue planes may prevent visualization of the nerves (23,26).…”
Section: Nervesmentioning
confidence: 99%